Encyclopedia of community from the village to the virtual world - Christensen, Karen 1957-; Levinson, David 1947- (Gale virtual reference library, 2003)
"This encyclopedia is a welcome exploration of the great variety of social networks that human beings create and participate in. Interdisciplinary in scope, the set includes contributions from some of the foremost scholars studying community today. Appendixes include an extensive bibliography, a collection of resources guides, an annotated guide to "Community in Popular Culture," and "Libraries Build Community," a guide for librarians."--"The Top 20 Reference Titles of the Year," American Libraries, May 2004.